Intercultural communicative competence: findings from competence-based approach - Zhumaliyeva, Rakhima; Muratkyzy, Akbota (Pedagogy and Psychology, 2020)
Globalization is a fact in our era arising from many various factors. The process and results of this phenomenon affect each nation, community and almost every single person somehow in almost all spheres. The current stage of development is characterized by the formation of the global challenges facing society, civilization as a whole, which inevitably impacts on the state of education. The demand of transition to a new Kazakhstan educational paradigm is a target for the implementation of competence-based approach. The study is dedicated to the logical, conceptual approach towards understanding of cognition, language and culture, which can be found in the fundamental works of researches on competency-based approach. Moreover, this paper describes the nature, mechanism and importance of forming intercultural-communicative competence of future specialists. This research is carried out within the framework of the Ministry of Education and Science of Republic of Kazakhstan grant project “Developing and implementing the innovative competency-based model of multilingual IT specialist in the course of national education system modernization”.